MANAGEMENT OF NON-PERFORMING ASSETS (NPA): A STUDY OF INDIAN COMMERCIAL BANKS (International Journal of Food and Nutritional Sciences, 2022)
The banking sector in India currently has non-performing assets (NPAs) that are both much lower than those of several economies and equivalent to those of numerous advanced economies. The RBI lists the decline in non-performing assets (NPAs) as one of the main accomplishments of the banking industry of India in the past year. However, the growing number of NPAs continues to be a major issue for the Indian banking industry. In general, Indian commercial banks have a propensity to understate their non-performing assets (NPA) ratios. One approach is to "ever-green" advancements by using subtle methods. The NPAs have negatively impacted banks' earnings potential and profitability. One of India's largest economic challenges is reducing non-performing assets (NPAs) in banks. This study aims to provide a basic diagnosis of the way commercial banks in India manage their non-performing assets (NPAs). Eventually, it has pinpointed a few of the gaps regarding the significant amount of bank non-performing assets (NPAs) and suggested tactics to address the unchecked outbreak of commercial bank viruses